Pengaruh Antrian BBM Solar Terhadap Kinerja Jalan Studi Kasus : (SPBU Yos Sudarso Dan SPBU Maluku) - Siti Nurfajrina J. Patunrangi; Jurair Patunrangi; Bryan Smyth Momongan (Jurnal Teknologi Berkelanjutan, 2025)
Abstract: To find out how much influence the diesel fuel queue has on traffic flow. As is the case with fuel stations on Yos Sudarso road and fuel stations on Maluku Road located in Palu City, Central Sulawesi Province. This study aims to evaluate the condition of vehicle queues and provide an overview of traffic flow fluctuations at Yos Sudarso fuel stations and Maluku fuel stations and their effect on road performance. The study used a survey method to obtain primary data obtained directly in the field. Data collection was carried out at 06.00 until 22.00, and the survey was conducted again at peak hours. The analysis carried out includes recording traffic volume, vehicle travel time and side obstacles passing at the observation point. From the results of research and data processing, it is obtained that the peak hour of traffic flow at the Maluku Fuel Station on Jalan Maluku on Wednesday occurs at 17.00 - 18.00, with road capacity when there is a queue of 2060.85 smp / hour with a low class of side obstacles and when there is no queue of 2060.85 smp / hour with a low class of side obstacles, the degree of saturation when there is a queue of 0.48 with level of service A, while when there is no queue 0.48 with level of service A. At Yos Sudarso Fuel Station on Thursday, the peak hour occurs at 17.00 - 18.00 with road capacity when there is a queue of 2469.60 smp / hour with moderate side obstacle class, while when there is no queue 2520.00 smp / hour with low side obstacle class. The degree of saturation when there is a queue is 0.78 with level of service C, while when there is no queue 0.76 with level of service C.